Disability : the basics - Shakespeare, Tom, 1966- (Abingdon, Oxon ; New York, NY : Routledge, 2018)
"Disability: The Basics is an engaging and accessible introduction to disability which explores the broad historical, social, environmental, economic and legal factors which affect the experiences of those living with an impairment or illness in contemporary society. The book explores key introductory topics including:the diversity of the disability experience;disability rights and advocacy;ways in which disabled people have been treated throughout history and in different parts of the world;the daily realities of living with an impairment or illness;health, education, employment and other services that exist to support and include disabled people;ethical issues at the beginning and end of life.Disability: The Basics aims to provide readers with an understanding of the lived experiences of disabled people and highlight the continuing gaps and barriers in social responses to the challenge of disability. This book is suitable for lay people, students of disability studies as well as students taking a disability module as part of a wider course within social work, health care, sociology, nursing, policy and media studies."--Provided by publisher.
chapter 1 Understanding disability -- chapter 2 Disability across time and place -- chapter 3 A life worth living -- chapter 4 Disabling barriers -- chapter 5 Health and social care -- chapter 6 Education for all -- chapter 7 A matter of life and death -- chapter 8 Advocacy and resistance.
Keywords: People with disabilities -- Social conditions; People with disabilities -- Great Britain -- Social conditions; Sociology of disabilities